EPIDEMIOLOGY OF BREAST CANCER PATIENTS ABOUT MENSTRUAL AND REPRODUCTIVE FACTORS IN SULAIMANI CITY - Omar, Kozheen Othman; Ali, Bushra Mohammed (Journal of Sulaimani Medical College, 2024)
Background Breast cancer is the most common disease in women globally and the main reason for cancer-related deaths among Iraqi women, making it a serious global public health concern. It is the most prevalent type of cancer among women in Sulaimani City Objective To determine the potential reproductive and menstrual cycle risk factors associated with breast cancer. Methodology This hospital-based case-control study was carried out through face-to-face interviews at Hiwa Hospital, the Shar Teaching Hospital, and the Shar Hospital Breast Cancer Centre (Mammography Centre). A sample of 310 participants was conveniently selected; 110 patients with confi rmed breast cancer (cases) and 200 women without breast cancer were considered a healthy control group. Data analysis was performed using SPSS version 26. Statistical signifi cance was determined using the Chi-square test and odds ratios (OR). A p-value of ≤0.05 was considered statistically signifi cant. Results According to our result, a mother age of primigravida above 30 years old is nearly fi fteen times more likely to get breast cancer OR =15.62, 95% CI: (3.84-47.41) P value <0.001. Shorter days in a period, particularly those lasting fewer than four days, are connected to an elevated risk of breast cancer OR =25.38, 95% CI:(2.72-236.7) P- value=0.005. Using birth control pills has been linked to a markedly increased risk of breast cancer, with an estimated odd ratio (OR) =4.24, 95% CI:(1.88-20.32) P-value=0.05. Then menarche, the menstrual cycle’s regularity, menopause, Parity, miscarriage, HRT (Hormonal replacement therapy), and PMS (premenstrual syndrome) have no association with breast cancer. Conclusion The mother’s age in primigravida is more than 30 years, hormonal birth control pills, and menstrual cycles of short duration are signifi cant risk factors associated with breast cancer.
Keywords: Breast cancer; menstrual cycle; reproductive factors; risk factors; Sulaimani